2022
DOI: 10.1093/gbe/evac153
|View full text |Cite
|
Sign up to set email alerts
|

Genome Evolution of a Symbiont Population for Pathogen Defense in Honeybees

Abstract: The honeybee gut microbiome is thought to be important for bee health, but the role of the individual members is poorly understood. Here, we present closed genomes and associated mobilomes of 102 Apilactobacillus kunkeei isolates obtained from the honey crop (foregut) of honeybees sampled from beehives in Helsingborg in the south of Sweden and from the islands Gotland and Åland in the Baltic Sea. Each beehive contained a unique composition of isolates and repeated sampling of similar isolates from two beehives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 90 publications
(105 reference statements)
2
14
0
Order By: Relevance
“…Based on the conventional assumption that bacterial assemblage in the crop primarily consists of transient microbes acquired via nectar foraging (3, 45, 47, 48), we expected a high degree of overlap among nectar, mouth, and crop samples. We did find high overlap between the nectar and the mouth, but to our surprise, most of the crop taxa were clearly distinct from those found in the nectar and the mouth (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the conventional assumption that bacterial assemblage in the crop primarily consists of transient microbes acquired via nectar foraging (3, 45, 47, 48), we expected a high degree of overlap among nectar, mouth, and crop samples. We did find high overlap between the nectar and the mouth, but to our surprise, most of the crop taxa were clearly distinct from those found in the nectar and the mouth (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…5). Apilactobacillus and Bombella , which are among the most commonly reported taxa in the crop of foraging adults, have also been found frequently in food stores, larvae, and queens (35, 45, 48, 5456). Although the data we present in this study are correlational, preventing us from establishing causal relationships, we speculate that the crop may serve as a consistent reservoir of these taxa that can influence the health of the adult bees and the larvae that they tend (3, 45).…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus is a well‐known probiotic, and A. kunkeei is common in the honey bee gut and colony environment and has been shown to produce bacteriocins that are better inhibitors of pathogenic bacteria (Dyrhage et al, 2022; Ebrahimi et al, 2021). In our previous study, we found that deltamethrin exposure increased the abundance of A. kunkeei and that it could help bees resist the effects of deltamethrin by modulating honey bee immunity (Dong et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps Wolbachia fails to persist in social bees because the established community protects against it, at least in the case of the most social corbiculates. Many features of the social bee core microbes already identified could play a part, such as priming the host immune system (Horak et al., 2020 ; Kwong, Mancenido, & Moran, 2017 ; Lang et al., 2022 ; Näpflin & Schmid‐Hempel, 2016 ) or the occurrence of direct antagonistic microbe–invader interactions (Dyrhage et al., 2022 ; Endo et al., 2012 ; Endo & Salminen, 2013 ; Koch & Schmid‐Hempel, 2012 ; Steele et al., 2017 ; Vásquez et al., 2012 ). Solitary bees – such as Andrena species (McLaughlin et al., 2023 ) – missing these interconnected communities would therefore lack the protection they confer and may become vulnerable to Wolbachia driven reproductive manipulation.…”
Section: Discussionmentioning
confidence: 99%